Control Design Of Robot Manipulator Position Based On Pd-Fuzzy Mamdani Controlled With Computed Torque Control (Pd-Fuzzy-Ctc) - Duli Ridlo Istriantono; Trihastuti Agustinah (Jurnal Teknik ITS, 2015)
Robotics science has evolved significantly, driven by rapid advances in computer and sensor technology; and theoretical advances in control and computer vision. These development make widespread use of robot manipulators in industrial environments. Major problem in controlling a robot manipulator is to control the robot in order to achieve the desired position. Therefore the design issue of the robot control is to choose the right type controller. Computed Torque Controller (CTC) is a powerful nonlinear controllers are widely used in the control of robot manipulators. CTC controller is designed based on feedback linearization and the required torque of the robot arm by using a nonlinear feedback control law. Simulation is done by providing joint trajectory from point to point. The simulation results show that the PD-Fuzzy-CTC controller is able to follow the joint trajectory with The RMSE value of the joint angle position of PD-Fuzzy-CTC controller is 10 times smaller than that of the PD-CTC controller with the end-effector position accuracy is 0.1 mm.